MODEL OF USAHA KESEHATAN SEKOLAH PELANGI (UKSP) ON CHILDREN ORAL HEALTH STATUS - Santoso, Bedjo; Sunarjo, Lanny; Sakbana, Boby Irsan (Postgraduate Program , Poltekkes Kemenkes Semarang, 2019)
Health development aims to improve community health status, but in health development there are still problems, especially health problems in elementary school children. Efforts made by the government in the form of the School Health Effort program and the success rate in each province averaged 13.6%, so a comprehensive model is needed in the school named the Model of Usaha Kesehatan Sekolah Pelangi. The aims is to produce the Model of Usaha Kesehatan Sekolah Pelangi in improving health status of children's dental and oral health status.In this research used Research and Development, there are five stages of research namely: information gathering, model design, expert validation and revision, model testing (using the quasi-experimental control group pretest and posttest design method and model results). The sample was divided into 2 groups namely the implementation of the Model of Usaha Kesehatan Sekolah Pelangi in the intervention group and the school health business program in the control group. Data were tested using intraclass correlation coefficient, chi-square, shapiro wilk, friedman, wilcoxon and mann-whitney.The results showed the school health business model is feasible as a model of education and health services shown with the value of p<0.031. The Model of Usaha Kesehatan Sekolah Pelangi is effective in increasing the performance treatment index (PTI) shown by the value of p<0.001 and decreasing the simplified oral hygiene index (OHI-S) indicated by the value of p<0.001.The conclusion of this research is Model of Usaha Kesehatan Sekolah Pelangi is effective in improving children's dental and oral health status.